Collective Incentives and Cooperation in Teams with Imperfect Monitoring - Friederike Mengel; Erik Mohlin; Simon Weidenholzer (Lund University, School of Economics and Management, Department of Economics, 2018)
We experimentally explore the role of collective incentives in sustaining cooperation in finitely repeated public goods games with imperfect monitoring. In our experiment players only observe noisy signals about individual contributions, while total output is perfectly observed. We consider sanctioning mechanisms that allow agents to commit to collective punishment in case total output fall short of a target. We find that cooperation is higher in the case of collective punishment compared to both the case of no punishment and the case of standard peer-to-peer punishment which conditions on the noisy signals. Further experiments indicate that both the commitment possibility and the collective nature of punishment matter for the positive effect of collective incentives on cooperation.
Keywords: C72; D02; D23; D90; 330; Public goods game; Team production; Punishment; Collective sanctions; Imperfect monitoring